PENINGKATAN KETERAMPILAN MENULIS KARANGAN NARASI MELALUI MODEL THINK PAIR SHARE DENGAN AUDIO VISUAL PADA SISWA KELAS IV SDN KANDRI 01 (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Indonesian language learning in elementary schools aims to develop students' language skills. Based on observations in fourth-grade students at SDN Kandri 01 Semarang, students' narrative writing skills are still low. Nineteen out of 36 students (52.8%) still received average daily test scores below the Minimum Completion Minimum (KKM) (65). This is due to teachers' lack of skills in implementing learning models and media. Researchers implemented the Think Pair Share learning model with audiovisual media to improve students' narrative writing skills. The research question is whether the Think Pair Share model with audiovisual media can improve teacher skills, student activity, and student learning outcomes in narrative writing. This study aims to: (1) improve teacher skills, (2) increase student activity, and (3) improve student learning outcomes in narrative writing. The research subjects were teachers and fourth-grade students at SDN Kandri 01. The results showed an increase in teacher skills, student activity, and student learning outcomes in narrative writing. In cycle I, meeting 1, the teacher's skills obtained a score of 25 with sufficient criteria, increasing in meeting 2 to 31 with good criteria. In cycle II, meeting 1, obtained a score of 35 with very good criteria, increasing in meeting 2 to 37 with very good criteria. Student activity in cycle I, meeting 1, obtained an average score of 23.2 with sufficient criteria, increasing in meeting 2 to 28.1 with sufficient criteria. In cycle II, meeting 1, obtained an average score of 24.8 with good criteria, increasing in meeting 2 to 29.6 with good criteria. The completeness of student learning outcomes in cycle I, meeting 1 was 70.6% with an average of 65.7, increasing in meeting 2 to 75% with an average of 67.9. In cycle II, meeting 1, the completeness of student learning outcomes was 81.3% with an average of 69.8, increasing in meeting 2 to 85.7% with an average of 72.4. Based on the research data, it can be concluded that implementing the Think Pair Share model with audiovisual media can improve teacher skills, student activity, and student learning outcomes in narrative writing. Recommendations for teachers include implementing appropriate learning models and media to improve student motivation and learning outcomes. One such model is the Think Pair Share model and audiovisual media. Keywords: narrative writing skills, Think Pair Share model, audiovisual media.